Hydrogen Sensors Based on Pd-Based Materials: A Review - Shubin Yan; Yuhao Cao; Yiru Su; Biyi Huang; Changxin Chen; Xianfeng Yu; Aiwei Xu; Taiquan Wu (Sensors)
Hydrogen is receiving a lot of attention from researchers as a clean energy source and one of the most promising sources of energy for the future. Detection of hydrogen before it reaches explosive conditions is a central issue in the safe use of hydrogen. Hydrogen sensors are devices that detect the hydrogen concentration in the environment and are capable of outputting an electrical signal proportional to the magnitude of the hydrogen concentration. Palladium (Pd) has become one of the preferred materials for the preparation of hydrogen sensors due to its strong hydrogen absorbing ability. In this paper, the intrinsic mechanism of hydrogen absorption by Pd metal is revealed, and the performance of various types of Pd-based hydrogen sensors is reviewed.